Exploring the Relationships between Structure and Antimicrobial Potency of Quinolinequinones - Emel Mataracı-Kara; Nilüfer Bayrak; Mahmut Yıldız; Hatice Yıldırım; Amaç Fatih TuYuN (MDPI AG, 2022)
Microorganisms are responsible for hospital infections, and methicillin-resistant Staphylococcus aureus is one of them. In looking for the most effective lead structures to cope with the rise of antimicrobial (antibiotic) resistance, we evaluated the antimicrobial profile of quinolinequinones for potential antimicrobial applications. 1,4-quinone molecules fused with heteroatom have been studied extensively for many years as a source of drugs and lead structures. The aims of this study were to evaluate the antimicrobial activity of quinolinequinones against bacterial and fungal strains, and to probe for potential lead structures. For this reason, the activity of these compounds against three different strains of Candida fungi (C. albicans, C. parapsilosis, and C. tropicalis) and Gram-positive and Gram-negative pathogenic bacteria were investigated, searching for potential lead compounds. Five of nine quinolinequinones showed activity mainly against the Gram-positive strains with a minimal inhibitory concentration within the Clinical and Laboratory Standards Institute (CLSI) levels. The results revealed that quinolinequinones have significant activity against bacteria including Staphylococcus aureus and Staphylococcus epidermidis, and fungi including Candida albicans and Candida parapsilosis. QQ1, QQ2, QQ3, QQ5, and QQ6 exhibited the highest growth inhibition against two essential species of the Gram-positive strains (Staphylococcus epidermidis and Staphylococcus aureus). Among these, four molecules (QQ2, QQ3, QQ5, and QQ6) were also active against Enterococcus faecalis, the other member of the Gram-positive strains. The antifungal profile of two quinolinequinones (QQ7 and QQ8) indicated that they were as effective as the reference drug Clotrimazole against Candida albicans. The same molecules also have potential inhibitory antifungal activity against Candida tropicalis. For better understanding, the most active two quinolinequinones (QQ2 and QQ6) were examined for biofilm inhibition and a time-kill kinetic study.